The impact of early bilingualism on controlling a language learned late: an ERP study - Martin, Clara D.; Strijkers, Kristof; Santesteban, Mikel; Escera, Carles; Hartsuiker, Robert J.; Costa, Albert (Frontiers in Psychology, 2013)
This study asks whether early bilingual speakers who have already developed a language control mechanism to handle two languages control a dominant and a late acquired language in the same way as late bilingual speakers. We therefore, compared event-related potentials in a language switching task in two groups of participants switching between a dominant (L1) and a weak late acquired language (L3). Early bilingual late learners of an L3 showed a different ERP pattern (larger N2 mean amplitude) as late bilingual late learners of an L3. Even though the relative strength of languages was similar in both groups (a dominant and a weak late acquired language), they controlled their language output in a different manner. Moreover, the N2 was similar in two groups of early bilinguals tested in languages of different strength. We conclude that early bilingual learners of an L3 do not control languages in the same way as late bilingual L3 learners –who have not achieved native-like proficiency in their L2– do. This difference might explain some of the advantages early bilinguals have when learning new languages.